MOVEMENT OF RESCUERS IN SNOWY REGIONS - Tokhir Ergashev (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Abstract. Rescue operations in snowy and icy environments require well-developed movement techniques, specialized equipment, and strict adherence to safety measures. Deep snow, icy surfaces, variable ice thickness, and low temperatures significantly complicate the movement of rescue personnel and increase physical load and operational risks. The effectiveness of search-and-rescue missions largely depends on the correct selection of movement methods, equipment, and transport means adapted to specific terrain and climatic conditions. This article analyzes the main methods of rescuers’ movement in snowy areas, including walking, the use of snowshoes, skis, sleds, snowmobiles, and all-terrain vehicles. Particular attention is paid to safe movement on icy surfaces, assessment of ice strength and thickness, group movement rules, and the use of anti-slip equipment and alpine gear. The paper also examines hazards associated with snow-covered ice, ice hummocks, spring thaw conditions, wetlands, and moving sea ice. The presented material emphasizes practical safety recommendations and technical solutions aimed at reducing physical fatigue, preventing accidents, and ensuring the safety and efficiency of rescuers during search-and-rescue operations in winter conditions.